Linear and nonlinear controllers of a solar photovoltaic water pumping system - M. Madark; A. Ba-razzouk; M. El Malah (Institute of Advanced Engineering and Science, 2020)
This paper provided a comparative study between linear and nonlinear controllers of a solar photovoltaic (PV) water pumping system using an induction motor and a centrifugal pump. For linear controller, classical Perturb and Observe was selected to ensure the operation of the PV system at the maximum power point (MPP) and is combined with Indirect Rotor Field Oriented Control (IRFOC) based on a conventional proportional integral speed regulator chosen to control and to optimize the rotor speed. In second and third controllers, Backstepping and first order sliding mode controls were proposed for controlling the whole system. To regulate and optimize rotor speed in the nonlinear controller, all considered control techniques were combined with IRFOC in order to establish easy control laws. In addition, MPP was tracked by acting on the DC-DC converter and using its mathematical model for developing control laws. Maximum delivered power was used as reference signal for optimizing actual rotor speed. The controlled system is operated without mechanical sensors. Estimators of rotor speed and load torque were proposed based on the mathematical model of induction motor and centrifugal pump and using only available output measurements.. Simulation results were investigated and the effectiveness of the nonlinear proposed strategies.